Wykorzystanie mediów społecznościowych w sektorze publicznym w kontekście wymogów wynikających z ogólnego rozporządzenia o ochronie danych - Lubasz, Dominik (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The article presents issues related to the growing use of social media in the public sector as a tool for the implementation of information and participation policy. It discusses the benefits of using modern techniques of information and communication, but also points to the problems of implementation, especially from the perspective of personal data protection requirements, proposing a model approach.
Keywords: social media; data transfer; transfer of data to third countries; personal data protectionreform; public administration; public sector entities; decisions of the DPA; personal data processing; public information